2011
DOI: 10.1111/j.1745-4530.2009.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultra High Hydrostatic Pressure on Concentrations of Limonene, Α‐terpineol and Carvone in Navel Orange Juice

Abstract: Response surface methodology (RSM) was used to compare the effects of the selected variables on the changes of concentrations of limonene,α‐terpineol and carvone by ultra‐high hydrostatic pressure (UHP) treatment. A Box–Behnken experimental design was used with control variables of pressure (100–500 MPa), temperature (20–40C) and treatment time (10–20 min). Pressure, temperature and treatment time were found to be critical factors influencing changes of concentrations. Both pressure and temperature could cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Carvone, which is a product of limonene oxidation (Pan et al . ), did not increase as expected in the samples that were exposed to oxygen in either manufacturer or consumer conditions (Fig. ).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Carvone, which is a product of limonene oxidation (Pan et al . ), did not increase as expected in the samples that were exposed to oxygen in either manufacturer or consumer conditions (Fig. ).…”
Section: Resultssupporting
confidence: 68%
“…Carvone is an important volatile because it is commonly used as a measure of degradation in orange juice quality (Pan et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The odor and fl avor (volatile content, 20 key aroma compounds) of the high-pressure-processed orange juice was acceptable to consumers even after storage for 12 weeks at lower temperatures of up to 10 °C (Baxter et al 2005 ). Pan et al ( 2011 ) demonstrated that limonene degradation in case of freshly squeezed navel orange juice increased with increasing processing pressure or temperature. The limonene degradation was found to result in significant increase of α-terpineol and carvone concentrations.…”
Section: Orangesmentioning
confidence: 97%